Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Pada PT. Miami Creameries - Alfina Damayanti; Ikhwan Maulana Haeruddin; Abdi Akbar Idris (Jurnal Manajemen Riset Inovasi, 2023)
The purpose of this research is to find out how rewards and punishment influence employee performance at PT. Miami Creameries. The sample used was 61 employees using saturated sampling technique. This research data collection used observation methods, interviews, distributing questionnaires and literature review. The data obtained was then analyzed using the multiple linear regression formula and hypothesis testing with the help of the SPSS (Statistical Package For Social Science) program. The regression equation formed is Y = 5,406 X1 + 0.305 + 0.808 X2. Simultaneous hypothesis testing: Reward and Punishment together influence employee performance. The magnitude of the influence of reward and punishment on employee performance with an Adjusted R square value of 69.7%. while the rest is influenced by other variables not included in this study.